Public health approaches to practice - Mitcheson, Jan (Cheltenham, UK : Nelson Thornes, 2008)
Series Information Providing complete support for the developing healthcare practitioner looking to move into areas of accountability and managerial responsibility. Enhancing the knowledge and skills of health care students and registered practitioners in public health approaches to preventative health care.
1. Public health policy -- 2. Principles and key concepts in public health practice -- 3. Public health approaches to practice -- 4. Assessing health needs -- 5. Using evidence in public health practice -- 6. Public health interventions -- 7. Working in partnership for public health -- 8. Evaluating public health approaches -- 9. Leading public health developments
Includes bibliographical references and index
Keywords: Public health nursing; Public Health Nursing -- methods; Preventive health services; Public Health Practice